Diversity of Mitochondrial Pathology in a Mouse Model of Axonal Degeneration in Synucleinopathies. (14th March 2013) - Sekigawa, Akio; Takamatsu, Yoshiki; Sekiyama, Kazunari; Takenouchi, Takato; Sugama, Shuei; Waragai, Masaaki; Fujita, Masayo; Hashimoto, Makoto
Abstract : There is mounting evidence for a role of mitochondrial dysfunction in the pathogenesis of α -synucleinopathies such as Parkinson's disease (PD) and dementia with Lewy bodies (DLB). In particular, recent studies have demonstrated that failure of mitochondrial quality control caused by loss of function of the PTEN-induced kinase 1 (PINK1, PARK6) Parkin (PARK2) pathway may be causative in some familial PD. In sporadic PD, α -synuclein aggregation may interfere with mitochondrial function, and this might be further exacerbated by leucine-rich repeat kinase 2 (LRRK2). The majority of these findings have been obtained in Drosophila and cell cultures, whereas the objective of this paper is to discuss our recent results on the axonal pathology of brains derived from transgenic mice expressing α -synuclein or DLB-linked P123H β -synuclein. In line with the current view of the pathogenesis of sporadic PD, mitochondria abnormally accumulated in α -synuclein/LRRK2-immunopositive axonal swellings in mice expressing α -synuclein. Curiously, neither mitochondria nor LRRK2 was present in the swellings of mice expressing P123H β -synuclein, suggesting that α - and β -synuclein might play differential roles in the mitochondrial pathology of α -synucleinopathies.